Environmentally Sensitive Management Approach Within the Scope of Carbon-Free Airport: The Case of Sivas Nuri Demirağ Airport - Serdar Kızılcan; Kağan Cenk Mızrak (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The aviation industry has been developing continuously from past to present. This development is not only limited to airplanes, but is effective in all fields of aviation. In this context, the increase in the number of passengers and flight points has increased the importance of airports. These increases have led to various additional requirements at airports such as airport positioning, large grounds, large facilities and technological systems. In addition to the fact that airports play an important role in the economic and social development of the region where they are located, the effects of environmental pollution are increasing. Environmental pollution is not only regional; The fact that it causes long-term global environmental effects has made it necessary to control the activities within the airport. For this reason, in Turkey, General Directorate Of State Airports Authority aims to control the possible effects of ongoing activities at airports on the environment, to leave a more livable world to the next generations with the measures taken against global warming and climate change, and to provide sustainable airport management. Because of this, carbon-free airport Project was started. In this study, information is given about the "Carbon-Free Airport Project" and the application principles of the project are mentioned. For this purpose, Sivas Nuri Demirağ Airport was inspected, which is one of the few airports within the scope of this project in Turkey, and suggestions were made in the light of this information.